234k views
2 votes
X=A- B/A. How to find A?



User Ofershap
by
4.6k points

1 Answer

7 votes

Answer:

A =
( x+√(x^2+4b))/(2), ( x-√(x^2+4b))/(2)

Explanation:

First manipulate the equation as such,


x=A-(B)/(A)


0=A - (B)/(A) - X


0=A^2 -AX - B

Then use the quadratic formula,


x= (-b\pm√(b^2-4ac) )/(2a) when,
0 = ax^2 +bx +c.

Which gives
A= ( x+√(x^2+4b))/(2), ( x-√(x^2+4b))/(2).

User Mike Richards
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.